2024
DOI: 10.1111/ene.16226
|View full text |Cite
|
Sign up to set email alerts
|

Genetic insights into the relationship between immune cell characteristics and ischemic stroke: A bidirectional Mendelian randomization study

Xia Deng,
Shuai Hou,
Yanqiang Wang
et al.

Abstract: Background and purposeIschemic stroke, a major contributor to global disability and mortality, is underpinned by intricate pathophysiological mechanisms, notably neuroinflammation and immune cell dynamics. Prior research has identified a nuanced and often paradoxical link between immune cell phenotypes and ischemic stroke susceptibility. The aim of this study was to elucidate the potential causal links between the median fluorescence intensity (MFI) and morphological parameters (MP) of 731 immune cell types an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…These findings suggest that CD39 plays an important role not only in inhibiting thrombosis, but also in reducing neuroinflammation. A recent study has found that CD39 emerges as a key immunomodulatory component for neuroprotection in ischemic stroke on CD39+ activated CD4 Treg cells ( 47 ). Similar to our results, an elevated proportion of CD39+ resting T cells, signifying a reduced proportion of activated CD39+ T cells, exerts an adverse influence on stroke.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that CD39 plays an important role not only in inhibiting thrombosis, but also in reducing neuroinflammation. A recent study has found that CD39 emerges as a key immunomodulatory component for neuroprotection in ischemic stroke on CD39+ activated CD4 Treg cells ( 47 ). Similar to our results, an elevated proportion of CD39+ resting T cells, signifying a reduced proportion of activated CD39+ T cells, exerts an adverse influence on stroke.…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 28 Linkage disequilibrium (LD) among SNPs was calculated based on the European 1000 Genome Reference panel. 29 To reduce the impact of LD and select independent SNPs, the clumping process (a threshold of LD r 2 < 0.001 within 10 000 kb distance) was conducted using PLINK software (version 1.90). 28 Weak IVs with an F‐statistic of <10 were excluded from further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…However, due to the exploratory nature of the study and our rigorous screening of IVs, adjusted significance levels were not considered the primary criteria for determining causal relationships, as in other similar MR studies. 29 , 34 …”
Section: Methodsmentioning
confidence: 99%
“…Following an ischemic event, there is a notable accumulation of B cells in the affected area, where they actively engage in the immune response ( 10 , 11 ). A previous Mendelian randomization (MR) study revealed that distinct B-cell subtypes exhibit differential impacts on IS, and this study posits that specific B-cell phenotypes, such as CD24+ B-cell phenotypes, potentially confer neuroprotection, in contrast to IgD+CD24-B cells, which may predispose individuals to a heightened risk of IS ( 12 ). Although this investigation offers preliminary insights, the intricate interplay and roles of IgD and CD24 phenotypes within the context of IS have yet to be comprehensively delineated, underscoring the critical necessity for this research.…”
Section: Introductionmentioning
confidence: 95%